Pengetahuan dan Pendapatan Akseptor KB dengan Penggunaan Alat Kontrasepsi Bawah Kulit (AKBK) - Lia Hartini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
This study aimed to determine the relationship between knowledge and income of family planning acceptors and subcutaneous contraception (AKBK) at BPM Habibah, Meat Jaya Village, in 2020. The research method used an analytic survey method with a Cross-Sectional approach. Univariate analysis results obtained from 50 respondents known that most respondents with good knowledge as many as 28 respondents (56%) more than those who lack awareness that is as much as 22 respondents (44%), a small proportion of respondents who have high incomes are 19 respondents (38%) more few of the low-income mothers were 32 respondents (62%). Those using under-skin contraception (AKBK) were 35 (70%) respondents. Based on the chi-square statistical test results on the relationship between knowledge (ρ value 0.011) and income (ρ value 0.042) with the use of AKBK. In conclusion, there is a significant relationship between knowledge and income with the use of under-the-skin contraception (AKBK) at BPM Habiba, Meat Jaya Urban Village, in 2020. Keywords: Family Planning Acceptor, Knowledge Contraception, Income